Applicatin of Blockchain Technology for E-Voting Systems Using Smart Contract - Denata Wijaya Aripin (Jurnal Indonesia Sosial Teknologi, 2025)
Blockchain technology has become a potential solution to improve security, transparency, and integrity in the e-voting system. This study examines the application of smart contracts in blockchain-based e-voting systems to reduce the risk of fraud and improve the efficiency of the voting process. The methods used include design and implementation prototype. The system uses the Ethereum platform, as well as security and performance analysis. The results demonstrate that smart contracts successfully enforce one-person-one-vote, automate vote verification and counting, and ensure that voting records are transparent, immutable, and publicly auditable while preserving voter privacy. Although scalability and transaction costs remain challenges for large-scale deployment, the proposed system significantly enhances the security, transparency, and trustworthiness of electronic elections. Therefore, blockchain technology combined with smart contracts represents a viable approach for developing secure and reliable e-voting systems. This study provides contribution in the development of a safe, transparent, and trustworthy e-voting system.